Beyond Dangdut: Nurturing Local Language Using Lyrics - Ferdi Arifin (Lembaga penelitian dan pengabdian kepada Masyarakat, 2019)
Endangered language issue recently becomes serious problem when government reports that there are 11 extinct local language in 15 days. Beside, The Language Development and Cultivation Agency has tried optimally to conserve local languages but it is not totally success. This study would take a critic againts goverment for language preservation and recommend to government for implementing new method for language preservation by using dangdut with local language usage in the lyrics. The method used in this study employs qualitatif and it thus applies language planning approach to find out the effectiveness of dangdut as for language preservation in industrial revolustion. The result shows recommendation to government to implies popular way for local language preservation through using dangdut songs with local language usage for the lyrics in order to enhance local language usage awarness among Indonesian.